Analisis Pengaruh Tingkat Pengangguran Terbuka Dan Kemiskinan Terhadap Pertumbuhan Ekonomi : Studi Komparasi Provinsi Lampung Dan Bengkulu - Alben Abimayu; Della Salsabila; Yuyun Anriyani; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was studied to analyze the factors that influence economic growth in the area. This research will focus on analyzing the relationship between the open unemployment rate, population and poverty on the island of Sumatra. The aim of this research is to provide a deeper understanding of the factors that influence economic growth on the island of Sumatra. Poverty is a problem that covers many aspects because it is related to low income, illiteracy, low health status and inequality between genders and a poor living environment (Word Bank, 2004). Overcoming the problem of poverty cannot be done separately from the problems of poverty, education, health and other problems that are explicitly closely related to the problem of poverty. Poverty is one of the problems faced by developing countries, including Indonesia.